THE URGENT NEED TO INFUSE LITERATURE CLASSES' SYLLABUS WITH CREATIVE INDUSTRY-ORIENTED COMPETENCE - Delvi Wahyuni (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This paper discusses the importance of infusing literature classes' syllabus with creative industry-oriented competence. In general, the objective of this measure is to keep literature relevant and matter to today's generation. who grow up immersed by gadgets and technology. It is a part of an ongoing research on developing teaching material for literature classes (poetry, prose and drama) which is compatible with creative industry, a recent trend in the global economic development. It is also an effort to respond to a preliminary research finding by Delvi Wahyuni (2014). in which students believed that studying drama (a genre in literary works) is important but it is not relevant in preparing them to enter the work force once they leave college. This paper consists of three main parts. First, it examines some classical advantages associated with literature as well as the practical benefit which students can get from studying literature and how they help them in getting a niche in the job market. Second, it discusses what literature class syllabus must contain to be deemed creative-industry-oriented. Third, this paper will provide a brief review on a working example ofa success story on creative industry and literature. All in all, the strengthened syllabus is expected to result in students seeing some congruity between what they leam and what is needed in to be able to compete in the ever increasingly competitive labor force, which most of the time not the case in the traditional literature syllabus. Finally, creative industry-oriented syllabus is effective in conforming the long held notion about literature and why it must be taught that it is dulce et utile (Sweet and useful).